Temporal trends and future projections of cysticercosis-induced epilepsy: insights from the global burden of disease study 2021- a cross-sectional study - Siyuan Yang; Xiaoyu Ji; Xuebo Sun (Frontiers in Public Health)
BackgroundThe burden of disability and a significant portion of early deaths linked to Cysticercosis are primarily due to epilepsy. This research sought to clarify the temporal patterns and forecast the future prevalence and years lived with disability (YLDs) associated with Cysticercosis-induced epilepsy (CIE), providing crucial information for the development of targeted prevention and treatment strategies.MethodsData from the 2021 Global Health database were used to measure the global, regional, and national burden of CIE by country, region, age, gender, and sociodemographic index (SDI). Age-period-cohort mode, the Auto Regressive Integrated Moving Average (ARIMA) model, and joinpoint regression analysis were also carried out.ResultsThe global prevalence and YLDs cases of CIE increased from 1992 to 2021, marking a 36.1 and 13.9% increase. However, the global prevalence and YLDs rates of CIE declined from 1992 to 2021, with estimated annual percentage change (EAPC) of −1.281 (95% CI: −1.373 to −1.19) and −1.878 (95% CI: −1.961 to −1.794). The age effect across global and SDI regions demonstrates an upward trend with advancing age, while unfavorable period effects are evident in high-SDI regions, where risk ratios for prevalence and YLDs exceed 1. The ARIMA model predicts a global rise in the total number of prevalence and YLDs cases from 2021 to 2036, with estimates reaching 4,955,416 (95% UI: 4,739,974 to 5,170,858) for prevalence and 2,032,208 (95% UI: 1,408,920 to 2,655,495) for YLDs by 2036.ConclusionThis study elucidates the complex epidemiological landscape of CIE, noting a global increase in prevalence and YLDs number against a decline in rates. Over the next 15 years, the burden of CIE is expected to remain significant, with high SDI regions warranting particular focus. The findings emphasize the necessity for region-specific strategies to mitigate the projected growth of CIE, highlighting the importance of tailored interventions.